Response of hybrid maize to boron application - Rahman, MS; Islam, MT; Ishtiaque, S; Sarker, MJU; Khan, AS MMR (Bangladesh Journal of Agricultural Research, 2018)
An experiment was carried out at farmer’s field of Kushtia district under High Ganges River Floodplain Soil (AEZ-11) during Rabi seasons of 2013-14, 2014-15 and 2015-16. The objectives of the study were to evaluate the effect of boron on the yield of hybrid maize (cv. BARI Hybrid Bhutta-9) and to find out the optimum dose of boron for higher yield and economic return. There were 6 treatments comprising 6 levels (0, 0.5, 1.0, 1.5, 2.0 and 2.5 kg B ha-1) of boron along with a blanket dose of N256 P65 K45 S27 Zn3 kg ha-1 and cowdung 5 tha-1. Boron fertility of the initial soil was in medium level (0.33 μg g-1). The experiment was conducted in RCB design with three compact replications. Results of three years study revealed that hybrid maize responded significantly to added boron for the first two years but for the third year the effect was statistically non significant. The highest grain yield was obtained with 2.5 kg B ha-1, which was marginally significant with boron control but statistically identical to rest of the boron levels. Although, the yield increased linearly up to 2.5 kg ha-1 but the effect was relatively better fitted with quadratic response function (R2 = 0.943). The mean highest grain yield found to be 8.55 t ha-1 for 2.5 kg B ha-1 against 8.20 t ha-1 from 0.5 kg B ha-1 and 7.84 t ha-1 from boron control. Considering the boron fertilty of soil, response of maize to boron and economic return, the optimum dose of boron may be 0.5 kg ha-1 for the cultivation of hybrid maize for medium level boron fertile soil under AEZ-11 of Kushtia district or alike. Bangladesh J. Agril. Res. 43(2): 281-288, June 2018